Efektifitas Media Audio Visual Terhadap Pengusaan Kosakata Siswa MI Al Ma’arif Samarinda - Mustamin, Mustamin; Hidayat, Ahmad Fadhel Syakir; Rachmasari, Fithri (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
The background of this research is that Arabic students at SD Al-Maaref Nahdlatul Ulama 003 Samaranda are still experiencing difficulties in mastering vocabulary and lack of interesting teaching aids in vocabulary teaching materials. This study aims to determine the ability to master Arabic vocabulary before and after the application of audio-visual aids and to determine the effectiveness of using audio-visual aids in mastering Arabic vocabulary in sixth grade students of Al-Maaref Nahdlatul Ulama Elementary School. 003 Samarinda. This research is a quantitative research. The type used is a quasi-experimental design with an asymmetric control group design. The population in this study were students of class VI SD Al-Maaref Nahdlatul Ulama 003 Smaranda. The sampling technique was purposive sampling obtained by class IV C with a total of 28 students as the experimental group and class IV D with a total of 20 students as the control group. This study uses data collection techniques, namely observation, documentation and tests. The statistics used to prove the hypothesis of data analysis are paired sample t-test and independent sample t-test. From the research results it is clear from the results of the descriptive analysis that the average post-test score for the experimental group using audio-visual aids was 80.20 and for the control class was 75.25. The results of the hypothesis analysis using the paired sample T test in the experimental group obtained a t value of 11.079 > 2.048 and a Sig (2-Tailed) value of 0.000, and an independent sample T test obtained a Sig (2-Tailed) value of 0.023 <0.05. Thus, it can be concluded that the use of audio-visual aids is effective in increasing Arabic vocabulary mastery at SD Al-Maaref Nahdlatul Ulama 003 Smaranda. Keywords: effectiveness, audiovisual aids, vocabulary mastery.